The divorce papers : a novel - Rieger, Susan, 1946- (Crown Publishers, 2014)
"The story of a high-profile, messy divorce, and the endearingly cynical young lawyer dragooned into handling it, told solely via personal correspondence, office memos, emails, articles, and legal papers"--